2013
DOI: 10.1007/s00405-013-2784-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human utricular otoconia degeneration in vital specimen and implications for benign paroxysmal positional vertigo

Abstract: Otoconia are assumed to be involved in inner ear disorders such as benign paroxysmal positional vertigo (BPPV). Up to now, the distinct structure and morphology of intact and degenerate human utricular otoconia has been only poorly investigated on vital specimen. In this study, human otoconia were obtained from the utricle in five patients undergoing translabyrinthine vestibular schwannoma surgery. Specimens were examined by environmental scanning electron microscopy. Intact and degenerate otoconia as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 25 publications
3
53
1
2
Order By: Relevance
“…Calcium and carbonate levels in the endolymph are critical for normal otoconial function, which is primarily provided by a calcium channel transport system expressed in the inner ear [14] . When the ultrastructural dysmorphology of human otoconia was investigated by Walther et al [15] , they found that otoconia may have various degrees of degeneration, from minor to major changes. In the major forms, profound morphological alterations, such as fractures with excessive loss of calcium-rich otoconia material, could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and carbonate levels in the endolymph are critical for normal otoconial function, which is primarily provided by a calcium channel transport system expressed in the inner ear [14] . When the ultrastructural dysmorphology of human otoconia was investigated by Walther et al [15] , they found that otoconia may have various degrees of degeneration, from minor to major changes. In the major forms, profound morphological alterations, such as fractures with excessive loss of calcium-rich otoconia material, could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the images obtained after formalin exposure reveal close structural similarities to degenerate otoconia as described in the literature showing pores and fissures in the belly area as well as fragment formation [3,7,8]. Given the results of this study and previous morphological observations, structural changes of otoconia may, in general, be induced within a short period of time during exposure to previously untested chemical agents [9][10][11][13][14].…”
Section: Discussionmentioning
confidence: 61%
“…Vital human otoconia were extracted as described recently [3]. Samples lying in the gelatinous matrix were identified by light microscopy (Axioplan 2 imaging, Carl-Zeiss) with a 300-fold magnification.…”
Section: Otoconia Samplesmentioning
confidence: 99%
See 2 more Smart Citations